The Investment Risk Of Banking Companies on IDX and The Effect Of Good Corporate Governance - Chairul Iksan Burhanuddin; Muhammad Nur Abdi; Amran Amran; Burhanuddin Burhanuddin (Universitas Muhammadiyah Sorong, 2022)
The goal of this research is to determine how good corporate governance affects investment risk. Managerial Ownership (X1), Institutional Ownership (X2), Independent Board of Commissioners (X3), Audit Committee (X4), and Investment Risk are some of the good corporate governance indicators considered in this study. The multiple linear regression analysis method was applied in this study. The participants in this study are banking businesses that were listed on the Indonesia Stock Exchange (IDX) between 2016 and 2018. Purposive sampling with preset criteria was used in the research sample. The goal of this research is to see if a company's effective corporate governance influences investment risk. The novelty of this research includes the current conditions on every aspect of the tested variables. Research results show that managerial ownership has a negative and insignificant effect on investment risk, Institutional ownership has a negative and insignificant effect on investment risk, The Independent Board of Commissioners has a negative and significant effect on investment risk, and the Audit Committee has a negative effect on investment risk, according to the findings of this study.